(untitled) (Journal of the College of Basic Education, 2022)
This study was conducted in the vegetal garden belonging to the Science Department / College Of Basic Education / University of Al-Mustansiriyah for the winter growth season 2015-2016 to see the effect of Increasing concentrations and levels for each growth regulator Gibberllin (GA3) and Potassium and the overlap between them in some of the in morphological and flora characters of Cumin Cuminum cyminum L. . The Cumin seeds planted in 1/11/2015 using Potassium levels 0,150 and 300 Kgm.h-1 added to the soil in addition to concentration of Gebberellic acid 0 ,50 and 100 mg.ltr-1 sprayed on the plants, The experiment designed as Randomized Complete Block Design with three replicates so this study included two factorial experiments 3×3×3 each experiment included 27 experimental units each area size was 1×1 m2 there were a daily follow-up for the experiments of the study to hold soil and yield services of irrigation , remove the bushes and fertilizing.The spraying of 100 mg.ltr -1 from Gibberllin led to an increase in plant height 23.25% , dry weight 23.25%, number of inflorescence 15.06%, number of flowers for the head inflorescence 23.19% and dropping in the number of branches 30.40% compared with the control treatment . Also the addition of level 300 Kgm.h-1of Potassium led to an increase in plant height 30.46%, dry weight 11.28%, number of inflorescence13.85%, number of flowers for the head inflorescence6.84 % and number of branches 35.66 % compared with the control treatment.The overlap between Gebberellic acid and Potassium gave a significant increase in some of the studied characters where the overlap between concentration 100 mg.ltr-1 Gebberellic acid and level 300 Kgm.h-1 Potassium led to increase in plant height 60.25%, dry weight 72.56%, number of inflorescence 26.49%, number of flowers for the head inflorescence 47.93 % and dropping in the number of branches 1.41% compared with the control treatment.